CARBON AND OXYGEN ISOTOPE COMPOSITION OF OXFORDIAN-EARLY KIMMERIDGIAN BELEMNITE ROSTRA: PALAEOENVIRONMENTAL IMPLICATIONS FOR LATE JURASSIC SEAS - Wierzbowski H. (My University, 2004)
Stable isotope analyses have been undertaken on Oxfordian–Early Kimmeridgian belemnite rostra derived from three palaeogeographic provinces of Europe: (1) the Boreal–Subboreal Province (Isle of Skye in Scotland); (2) the Submediterranean Province (central Poland and southern Germany); and (3) the Mediterranean Province (Pieniny Klippen Belt in the Western Carpathians). The samples have been screened for possible diagenetic alteration by using cathodoluminescence and trace element analyses and have been found to be largely well-preserved. Calculated palaeotemperatures (10–15°C) and analyses of belemnite habitats suggest that the Boreal–Subboreal belemnites were living in a relatively shallow sea (not deeper than 100–150 m) while the other belemnites possibly inhabited deeper neritic environments. Despite the influence of a vital effect, the δ13C values of belemnite rostra are interpreted to reflect primary variations in the oceanic carbon isotope signal. The fairly uniform Submediterranean δ13C values indicate a similar isotope composition of dissolved inorganic carbon (DIC) in the area of sedimentation of sponge megafacies in the deep Tethyan shelves. The slightly lowered δ13C values of some Mediterranean belemnites might occur due to upwelling providing 12C enriched bottom waters onto the area of the Czorsztyn Ridge in the Oxfordian. The discernibly more positive (1–2.5‰) δ13C values of Boreal–Subboreal belemnites are related to a high biologic productivity and a high organic matter burial in the partly isolated Boreal Sea. The stated differentiation in carbonate δ13C values distinctly exceeds present-day differences in isotope composition of seawater DIC.
Keywords: stable isotope; belemnites; Oxfordian-Early Kimmeridgian; Boreal-Subboreal Province; Submediterranean Province; Mediterranean Province; Mesozoic::Jurassic::Upper::Kimmeridgian; Мезозой::Юрская::Верхний::Киммериджский; Mesozoic::Jurassic::Upper::Oxfordian; Мезозой::Юрская::Верхний::Оксфордский